The role of blood CXCL12 level in prognosis of coronary artery disease: A meta-analysis - Zhang, Shunrong; Ding, Yu; Feng, Fei; Gao, Yue (Frontiers in Cardiovascular Medicine, 2022)
Objective: The role of C-X-C motif chemokine 12 (CXCL12) in atherosclerotic cardiovascular diseases (ASCVD) has emerged one of the research hotspots in recent years. Studies reported that higher blood CXCL12 level was associated increased major adverse cardiovascular events (MACEs), but the results were inconsistent. The objective of this study was to clarify the prognostic value of blood CXCL12 level in patients with coronary artery disease (CAD) through meta-analysis. Methods: All related studies about the association between blood CXCL12 level and prognosis of CAD were comprehensively searched and screened according to inclusion criteria and exclusion criteria. The quality of the included literature was evaluated with Newcastle-Ottawa Scale (NOS). Heterogeneity test was conducted, and pooled hazard risk (HR) or odd ratio (OR) with 95% confidence interval (CI) was calculated used fixed effect or random-effects model accordingly. Publication bias was evaluated with the Begg’s funnel plot and Egger’s test. Sensitivity analysis and subgroup analysis were also conducted. Results: A total of 12 original studies with 2959 CAD subjects were included into the final data combination. The pooled data indicated a significant association between higher CXCL12 level and MACEs both in univariate analysis (HR 5.23, 95% CI 2.48-11.04) and multivariate analysis (HR 2.53, 95% CI 2.03-3.16,) in CXCL12 level as category variable group. In CXCL12 level as continuous variable group, the result also indicated higher CXCL12 level significantly predicted future MACEs (multivariate OR 1.55, 95% CI 1.02-2.35). No significant publication bias was found in this meta-analysis. Conclusion: Higher blood CXCL12 level is associated with increased major adverse cardiovascular events in patients with CAD, blood CXCL12 level may serve as an important prognostic index for CAD. Integrating blood CXCL12 level into CAD risk assessment tools may provide more comprehensive messages for evaluating and managing CAD patients.